2021
DOI: 10.1093/brain/awab479
|View full text |Cite
|
Sign up to set email alerts
|

Junctional instability in neuroepithelium and network hyperexcitability in a focal cortical dysplasia human model

Abstract: Focal cortical dysplasia (FCD) is a highly epileptogenic cortical malformation with few treatment options. Here we generated human cortical organoids from patients with FCD type II. Using this human model, we mimicked some FCD hallmarks, such as impaired cell proliferation, the presence of dysmorphic neurons and balloon cells, and neuronal network hyperexcitability. Furthermore, we observed alterations in the adherens junctions zonula occludens-1 and partitioning defective 3, reduced polarization of the actin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Deep sequencing revealed somatic MTOR mosaicism in both the basal ganglia and overlying cortex. The somatic MTOR c.4375G > C (p.Ala1459Pro) variant is recently reported in an individual affected by FCDIIb 8 . In addition, variants affecting the same amino acid residue including c.4375G > T (p.Ala1459Ser) and c.4376C > A (p.Ala1459Asp) are associated with FCD and HME 1,2,9–11 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Deep sequencing revealed somatic MTOR mosaicism in both the basal ganglia and overlying cortex. The somatic MTOR c.4375G > C (p.Ala1459Pro) variant is recently reported in an individual affected by FCDIIb 8 . In addition, variants affecting the same amino acid residue including c.4375G > T (p.Ala1459Ser) and c.4376C > A (p.Ala1459Asp) are associated with FCD and HME 1,2,9–11 .…”
Section: Discussionmentioning
confidence: 98%
“…The somatic MTOR c.4375G > C (p.Ala1459Pro) variant is recently reported in an individual affected by FCDIIb. 8 In addition, variants affecting the same amino acid residue including c.4375G > T (p.Ala1459Ser) and c.4376C > A (p.Ala1459Asp) are associated with FCD and HME. 1 , 2 , 9 , 10 , 11 The alanine 1459 residue is located within the FAT domain of the MTOR protein, and functional assays have shown that the alanine to proline substitution results in hyperactivation of the mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical organoids offer an invaluable platform to study neurodevelopmental disease 31 , 43 , 44 and may offer insight into molecular mechanisms that contribute to aberrant phenotypic expression in individuals with WS, such as hypersociality. 9 We found transcriptomic dysregulation in GTF2I -KO cortical organoids compared to controls, including decreased expression of genes involved in synaptic structure and function, particularly glutamatergic function, and enriched expression of genes in pathways involved in cell death.…”
Section: Discussionmentioning
confidence: 99%
“…hPSC-derived brain organoids patterned towards the cerebral cortex are a valuable model that captures the 3D multicellular interactions occurring in vivo in cortical tissue. [1][2][3][4][5][6][7][8][9][10] During cortical development, neural progenitor cells undergo successive steps of neurogenesis and gliogenesis to generate first deep layer then upper layer glutamatergic neuron subtypes, astrocytes, and oligodendrocytes. Developing hPSC-derived cortical organoids recapitulate this sequence of in vivo cell production.…”
Section: Introductionmentioning
confidence: 99%